Enhancing Problem Solving by Improving the Identification of Root Causes to Avoid Reoccurring Non-conformances - Ask, Christoffer; Trygged, Maria (My University, 2016)
GKN Aerospace is the first tier supplier to the global aviation industry and produces products with a great complexity and quality. However, GKN is as many other producing companies confronted with internal reoccurring problems in the manufacturing. Reoccurring problems consume resources in terms of material and time for the employees. This case study was made with the purpose to identify possible improvement areas for the problem solving process at GKN in order to make it more robust. GKN are aware of that they have reoccurring non-conformances in manufacturing, they are measured, but the level is quiet constant. Through interviews, survey and review of internal documents the researchers found that there is room for improvement for the information collected and documentation. The initial documentation of non-conformances is sometimes poor. In addition, the problem characterisation made in the documentation template PPL is occasionally performed poorly, lacking useful information. The following root cause analysis has sometimes shortcomings in the method of breaking down the causes to identify the root cause. The literature study made suggests a more extensive way of working with the root cause analysis tool 5 Why, compared to how GKN works today. By studying the prerequisites to identify the root cause the authors found some possibilities for improvements. More time is needed for problem solving. Currently the time is insufficient, 95 % of the Production Engineers agree upon this. Further, the Operators must be more incorporated in the problem solving to understand the purpose of performing a good problem solving. They need to get proper education on the subject in addition to their expertise. In general the thesis concerns the understanding of how information is used and affects the problem solving as a whole. At GKN training is needed to emphasize the importance of problem characterization, to be able to identify root causes for problems. What GKN gains on illuminating focus on the problem characterization, the problem descriptions and the root cause analysis with improved prerequisites, is that GKN improves the process of identifying root causes of problems and thereby can avoid reoccurring non-conformances.
Keywords: Produktion; Hållbar utveckling; Produktionsteknik; Production; Sustainable Development; Manufacturing engineering